Análise comparativa da ação antimicrobiana do cimento endodôntico Acroseal associado diferentes concentrações de nanopartícula de prata sobre o biofilme de Enterococcus faecalis - Barboza, Jaqueline Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The failure of endodontic treatment is related to the persistence of infections in the root canal system, such as Enterococcus faecalis, so the use of dental cements should prevent bacterial recolonization and biofilm formation. For this reason, various dental cements have antimicrobial agents in their formulas. Silver nanoparticles have shown effective antimicrobial activity against the biofilm of Enterococcus faecalis. The objective of the present study was to evaluate the antimicrobial action of Acroseal dental cement, which is based on its formulation calcium hydroxide, associated to different concentrations of silver nanoparticles after prey, in an in vitro biofilm model. In order to perform the study, 160 dentin specimens (n = 8) were placed on plates containing Enterococus faecalis inoculated culture medium (ATCC 29212) to allow biofilm formation. After the formation period, the specimens were washed in saline solution and transferred to another plate where the discs of the cements to be tested were placed on the formed biofilm. The culture plates were left in an oven at 37 ° C for 2, 7 and 14 days. Specimens without cement application were used as controls for each experimental time. After each experimental time of contact with the cement, the specimens were washed in saline solution, vortexed, diluted and plated in triplicate in specific culture media. The colony forming units were counted and analyzed statistically (p <0.05) to determine the antimicrobial potential. The data were analyzed statistically using the one-way ANOVA, Shapiro-Wilkand Kruskal-Wallis test (p <0.05) to determine the antimicrobial potential. The results showed that the different concentrations of silver nanoparticle associated with Acroseal dental cement obtained effective antimicrobial action in the experimental time of 7 days in contact with the E. faecalis biofilm. However, there was no increase in antibacterial...

O insucesso do tratamento endodôntico está relacionado com a persistência de infecções no sistema de canais radiculares, como por exemplo Enterococcus faecalis, assim o uso de cimentos endodônticos deve prevenir a recolonização bacteriana e a formação do biofilme. Por esta razão, vários cimentos endodônticos têm em suas fórmulas, agentes antimicrobianos. Nanopartículas de prata têm mostrado atividade antimicrobiana efetiva contra o biofilme de Enterococcus faecalis. O presente estudo tem por objetivo avaliar comparativamente a ação antimicrobiana do cimento endodôntico Acroseal, que tem como base em sua formulação o hidróxido de cálcio, associado a diferentes concentrações de nanopartículas de prata pós presa, em um modelo de biofilme in vitro. Para a realização do estudo foram confeccionados 160 espécimes de dentina (n=8) que permaneceram em placas contendo meio de cultura inoculado com Enterococus faecalis (ATCC 29212) para permitir a formação de biofilme. Decorrido o período de formação, os espécimes foram lavados em solução salina e transferidos para outra placa onde os discos dos cimentos a serem testados foram colocados sobre o biofilme formado. As placas de cultura foram deixadas em estufa a 37°C por 2, 7 e 14 dias. Espécimes sem aplicação dos cimentos foram utilizados como controle para cada tempo experimental. Após cada tempo experimental de contato com o cimento, os espécimes foram lavados em solução salina, agitados em vortex, diluídos e plaqueadas em triplicata em meio de cultura específicos. As unidades formadoras de colônia foram contadas e analisadas estatisticamente (p<0,05) para determinação do potencial antimicrobiano. Os dados foram analisados estatisticamente usando os teste one-way ANOVA, Shapiro-Wilkand Kruskal-Wallis (p<0.05) para determinar o potenciala...
Keywords: Endodontia; Enterococcus faecalis; Nanopartículas; Prata; Endodontics